Longevity and Mortality of Boreal Woodland Caribou (Rangifer tarandus caribou) of the Dehcho Region, Northwest Territories - Larter, Nicholas C; Allaire, Danny G (The Canadian Field-Naturalist, 2016)
As part of an ongoing study of the ecology of boreal Woodland Caribou (Rangifer tarandus caribou), we investigated death sites of collared caribou to collect biological samples and determine a cause of death. The teeth collected from 25 adult females that had died since being radio collared were aged by cementum analysis. The age at death for one caribou was 22 years; this was only the second caribou tooth among 42 776 aged at a commercial laboratory found to be that old. An additional six of the 25 caribou were 13–17 years old at time of death. All but one of these seven female caribou had calved at least once during the periodthey were radio collared and monitored.